Barricada internacional : . Barricada internacional : semanario internacional del Frente Sandinista de Liberación Nacional
Since (1985) subtitled: Semanario internacional del Frente ... Engl. ed.: Barricada internacional. International weekly ... (ZF 65013). For the right numbering of the issues look in the colophon.